Cognitive Training and Transcranial Direct Current Stimulation in Mild Cognitive Impairment: A Randomized Pilot Trial - Das, Namrata; Spence, Jeffrey S.; Aslan, Sina; Vanneste, Sven; Mudar, Raksha; Rackley, Audette; Quiceno, Mary; Chapman, Sandra Bond (Frontiers in Neuroscience, 2019)
Background: Transcranial direct current stimulation (tDCS), a non-invasive stimulation, is an intervention to enhance cognition across clinical populations including Alzheimer's disease and mild cognitive impairment (MCI). This randomized clinical trial in MCI investigated the effects of anodal tDCS (a-tDCS) delivered to left inferior frontal gyrus (IFG) combined with gist-reasoning training (SMART) versus sham tDCS (s-tDCS) plus SMART on measures of cognitive and neural changes in regional cerebral blood flow (CBF). We were also interested in SMART effects on cognitive performance regardless of the tDCS group. Methods: 22 MCI participants completed a baseline cognitive assessment (T1) were randomized into one of two groups: a-tDCS+SMART and s-tDCS+SMART. Of which, 20 participants completed resting pCASL MRI scan to measure CBF. Eight SMART sessions were administered over four weeks with a-tDCS or s-tDCS stimulation for 20 minutes before each session. Participants were assessed immediately (T2) and 3-months after training (T3). Results: Significant group x time interactions showed cognitive gains at T2 in executive function (EF) measure of inhibition [DKEFS- Color word (p=0.047)], innovation [TOSL (p=0.01)] and on episodic memory [TOSL (p=0.048)] in s-tDCS+SMART but not in a-tDCS+SMART group. Nonetheless, the gains did not last for three months (T3) after the training. A voxel-based analysis showed significant increase in relative CBF in the right middle frontal cortex (MFC) (cluster-wise p=0.05, k=1,168 mm3) in a-tDCS+SMART compared to s-tDCS+SMART. Irrespective of the groups, the combined MCI showed gains at T2 in EF of conceptual reasoning [DKEFS card sort (p=0.033)] and category fluency [COWAT (p=0.055)], along with gains at T3 in EF of verbal fluency [COWAT (p=0.009)]. However, no significant relationship was observed between the increased CBF with cognition. Conclusion: One intriguing finding is a-tDCS to left IFG plus SMART increased blood flow to right MFC, however, the stimulation attenuated cognitive benefits of SMART on EF and memory compared to s-tDCS+SMART group. This paper contributes to growing evidence that cognitive training provides a way to significantly enhance cognitive performance in adults showing memory loss, where the role of a-tDCS in augmenting these effects need further study.